EVALUASI PENERAPAN RISK BASED AUDIT UNTUK MENINGKATKAN NILAI TAMBAH STUDI KASUS PADA PT BANK XYZ - , Eko Yulianto, Dr. Hardo Basuki, M.Soc.Sc., CSA. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
This paper aims to evaluate the application of risk-based audit (RBA), which includes the evaluation of eligibility, phase and implementation of RBA to provide value added in order to enhance the role and functions of the internal audit unit as a strategic business partner. This paper evaluated the implementation of risk based audit at Bank XYZ. Then explain the weakness in the application of risk-based audit especially in the preliminary audit report in order to produce findings that add value. The results showed that there are some weaknesses. Key performance indicators have not been used as the basis in selecting risks so the audit findings and recommendations resulting less strategic for performance improvement, risk selection conduct at the group level in the organizational structure so the audit findings are not complete (symptoms) and the format of preliminary audit report has not met the audit process that mainly related to the identification/selection activities and risk of the auditee.